Investigation of Extracellular Vesicles From SARS-CoV-2 Infected Specimens: A Safety Perspective - Nunez Lopez, Yury O.; Casu, Anna; Pratley, Richard E. (Frontiers in Immunology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic, caused by the SARS-CoV-2 virus, is wreaking havoc around the world. Considering that extracellular vesicles (EVs) released from SARS-CoV-2 infected cells might play a role in a viremic phase contributing to disease progression and that standard methods for EV isolation have been reported to co-isolate viral particles, we would like to recommend the use of heightened laboratory safety measures during the isolation of EVs derived from SARS-CoV-2 infected tissue and blood from COVID-19 patients. Research needs to be conducted to better understand the role of EVs in SARS-CoV-2 infectivity, disease progression, and transmission. EV isolation procedures should include approaches for protection from SARS-CoV-2 contamination. We recommend the EV and virology scientific communities develop collaborative projects where relationships between endogenous EVs and potentially lethal enveloped viruses are addressed to better understand the risks and pathobiology involved.